Esporotricose na gestação: relato de cinco casos numa epidemia zoonótica no Rio de Janeiro, Brasil Sporotrichosis in pregnancy: case reports of 5 patients in a zoonotic epidemic in Rio de Janeiro, Brazil - Rosane Orofino Costa; Andrea Reis Bernardes-Engemann; Luna Azulay-Abulafia; Fabiana Benvenuto; Maria de Lourdes Palermo Neves; Leila Maria Lopes-Bezerra (Sociedade Brasileira de Dermatologia, 2011)
Os autores apresentam cinco casos de esporotricose em gestantes numa epidemia zoonótica no Rio de Janeiro. São discutidos principalmente os aspectos clínicos e as dificuldades na escolha terapêutica desse grupo específico de pacientes. Five cases of sporotrichosis occurring in pregnant women in a zoonotic epidemic in Rio de Janeiro, Brazil, are described. The main clinical features, as well as the challenging therapeutic choices for this specific group of patients, are discussed.